4′-Hydroxybiphenyl-4-carboxylic acid - Feng, Sun (International Union of Crystallography, 2008)
The title compound, C(13)H(10)O(3), has potential oxygen donor and acceptor sites. Intermolecular hydrogen bonding between neighboring carboxylate groups leads to the formation of hydrogen-bonded dimers [graph-set motif R (2) (2)(8)]. A second hydrogen-bonding interaction between the hydroxy groups generates a chain and extends the structure into a lamellar layer. One of the benzene rings is disordered over two positions with an occupancy ratio of 0.57 (2):0.43 (2).